Enhancing Ethical Behaviors through Mindfulness, Spirituality, and Internal Control Systems at Religious-Based Higher Education Institutions - Aryawati, Ni Putu Ari; Iqbal, Achmad; Suka Ardiyasa, I Nyoman; Husain, Saddan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
Fraudulent activities, driven by both desire and opportunity, pose significant risks to organizations, leading to financial losses and undermining ethical standards. This study examines a moderated model of internal control on organizational ethical behaviors, mediated by mindfulness and spirituality. The proposed model was tested using partial least squares structural equation modeling (PLS-SEM) in SmartPLS3, with survey data from 32 religious state universities in Indonesia. The findings indicate that internal control structures enhance operational effectiveness and efficiency, the reliability of financial reporting, and compliance with laws and regulations at State Religious Universities in Indonesia. Internal control effectiveness mediates the relationship between internal control structure and organizational ethical behavior. Furthermore, organizational awareness and spirituality moderate the relationship between internal control structure and internal control effectiveness, as well as organizational ethical behavior, elucidating the conditions necessary for an effective internal control structure to achieve good university governance.